PENERAPAN AKUNTANSI BERDASARKAN SAK EMKM PADA DIAN LAUNDRY SANGATTA - Angga Kusumah; Nuuridha Matiin; Raudatul Jannah (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2022)
The purpose of this study was to determine whether Dian Laundry Sangatta implemented the preparation of financial statements based on SAK EMKM. This research is a comparative descriptive study, with more of a description of the results of interviews and documentation studies as well as comparing theory and reality in the field. The data that has been obtained will be analyzed qualitatively and described in descriptive form. Based on the research that has been done, Dian Laundry has not carried out journal recording and summarization activities in accordance with existing accounting standards, so there needs to be improvements and additions to the activities of this stage and Dian Laundry also does not have and prepare financial reports in accordance with SAK EMKM.